Canadian Higher Education and the Carnegie Foundation for the Advancement of Teaching Pension Plan - Lang, Daniel W. (Canadian Journal of Higher Education, 2022)
When the Carnegie Foundation was established in 1905, universities in Canada and Newfoundland were eligible for grants, on strict conditions that were seen by some as “colonial,” “continentalist,” or “imperial” intrusions on autonomy; for example, a Carnegie plan to create a federation of Maritime universities. This is a study of how Canadian universities found ways to comply with the requirement, of the compromises they had to make, or chose not to make, in governance, and of an ultimate shift in balance from sectarian to secular, and independent to publicly supported.